2018
DOI: 10.1101/364000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling of urine bacterial DNA to identify an “oncobiome” in a mouse model of bladder cancer

Abstract: Introduction: Recurrent urinary tract infections have been linked to increased risk of bladder cancer, suggesting a potential role of the urinary microbiome in bladder cancer pathogenesis.Objective: Compare the urinary microbiomes in mice with and without bladder. Methods:Longitudinal study of mice exposed to a dilute bladder-specific carcinogen (0.05% nbutyl-n-(4-hydroxybutyl) nitrosamine, BBN mice, n=10), and control mice (n=10). Urine was sampled monthly from individual mice for 4 months. Microbial DNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
2
1
Order By: Relevance
“…Mice being classified as pets in some communities, could be a source of transmission of pathogens to humans [12]. In contrast to this study, Forster et al [13] found eight (08) bacteria in the urinary microbiome of mice including betaproteobacter, acetobacter, Escherichia, Kaistobacter, Roseococcus, Rubellimicrobium and Sphingomonas. This difference in the abundance and nature of the species identified would be related to the environment or habitat of the mice, which is not the same, and to the method used to characterize the microbiome.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Mice being classified as pets in some communities, could be a source of transmission of pathogens to humans [12]. In contrast to this study, Forster et al [13] found eight (08) bacteria in the urinary microbiome of mice including betaproteobacter, acetobacter, Escherichia, Kaistobacter, Roseococcus, Rubellimicrobium and Sphingomonas. This difference in the abundance and nature of the species identified would be related to the environment or habitat of the mice, which is not the same, and to the method used to characterize the microbiome.…”
Section: Discussioncontrasting
confidence: 66%
“…This difference in the abundance and nature of the species identified would be related to the environment or habitat of the mice, which is not the same, and to the method used to characterize the microbiome. In the study of the mice urinary microbiome, Forster et al [13] proceeded by targeted sequencing of the V3 region of the 16S rRNA gene. This technique is more discriminating than the isolation technique on bacterial culture medium and allows to highlight a great specific diversity of the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria may affect the formation and progression of malignancies through pathways, such as susceptibility, inflammatory cytokines, and host immunity [ 8 ]. The role of bacteria in the development of bladder cancer has been proposed [ 9 ], but the evidence was weak when pooling data from more high-quality reports in a review by Bayne et al [ 10 ].…”
Section: Introductionmentioning
confidence: 99%